Lietuvos TSR bibliotekininkų, bibliografų ir informatikų publikacijų srauto sąjunginėje profilinėje periodinėje spaudoje analizė - Motiekienė, Vilija; Stirpeikaitė, Olga (Knygotyra, 1988)
Research work has become more intensive in recent years in the field of bibliography, library, and information sciences. A greater number of research works analyzing different issues of these sciences are being published. The present paper addresses one structural aspect of the problem concerning the contribution of Lithuanian bibliography, library, and information scientists to the development of science in the USSR. The paper analyzes the contribution of articles by Lithuanian SSR authors published in the union’s profile periodical press. Several research works, analyzing the contribution of countries, scientific groups, or scientists to the development of science, have been published in the Soviet Union and abroad. An index that helps address the tasks formulated in the article has been created using some of the statements provided in these works.